2014
DOI: 10.1155/2014/965350
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Study of Electrical Properties of SbTeI

Abstract: Needle shaped SbTeI crystals were obtained by solid state reaction. Electrical resistance was measured in the temperature range of 4 K to 550 K. SbTeI shows a metallic behavior from 4 K to 300 K, and at higher temperature (>300 K), it shows semiconducting behavior. Unlike SbSI, this material shows almost zero resistance around 550 K. It shows a piezoelectric behavior with a capacitance of 717 pF and its carrier density and nobilities are found to be 2.12 × 1016 cm−3 and 1.01 cm2/(V·s), respectively. Crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Moreschiniet et al [16] investigated the surface states using the QUANTUM-ESPRESSO package. Dubeyet et al [17] observed that SbTeI showed metallic behavior from 4 K to 300 K and semiconducting behavior at higher temperature (>300 K). Landolt et al [18] investigated the three dimensional bulk states and the two dimensional surface states using the GGA.…”
mentioning
confidence: 99%
“…Moreschiniet et al [16] investigated the surface states using the QUANTUM-ESPRESSO package. Dubeyet et al [17] observed that SbTeI showed metallic behavior from 4 K to 300 K and semiconducting behavior at higher temperature (>300 K). Landolt et al [18] investigated the three dimensional bulk states and the two dimensional surface states using the GGA.…”
mentioning
confidence: 99%
“…SbSeI was produced from mixture of antimony (Sb), selenium (Se) and iodine (I) elements [11]. Dubey et al (2014), reported that Nitsche and Merz [12] have synthesized materials like SbSI, SbSBr, SbSeBr, SbSeI, SbTeI, BiSCl, BiSBr, BiSI, BiSeCl, and BiSeBr. They studied their photoconducting properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…Dubey et al (2014), reported that Nitsche and Merz [12] have synthesized materials like SbSI, SbSBr, SbSeBr, SbSeI, SbTeI, BiSCl, BiSBr, BiSI, BiSeCl, and BiSeBr. They studied their photoconducting properties [8]. Many studies have been carried out on the electrical conductivity [13], electronic, thermoelectric [11], microelectronic, and optoelectronic [1] properties, reflectivity and vibrational spectrum [18] of SbSeI.…”
Section: Introductionmentioning
confidence: 99%